Fiqh Reference Patterns of the Majelis Taklim in Central Kalimantan - Helim, Abdul; Patrajaya, Rafik; Hosen, Nadirsyah; Warman, Arifki Budia; Benevolent, Wafid Syuja' Vennovary (El-Mashlahah, 2024)
Majelis taklim (known as taklim assemblies or taklim council) in Central Kalimantan uses different references in conveying and discussing fiqh material. This leads to a mixture of ideologies, for example, there are indications of deception in using fiqh references. Hence, the research aimed to find out the pattern of fiqh references used by majelis taklim in Central Kalimantan. It used empirical legal research with a sociological juridical type and a socio-legal approach. The research showed the fiqh references used by the majelis taklim  appear with various ideologies. And, four fiqh reference patterns were found, including the tendentious, the comparative and a mixture of ideologies or non-schools of thought, the pattern with organizational ideology, and the pattern referring towards the Syafi'i school of thought. From the four characteristics, it seems that the tendentious fiqh pattern, either tarjih maqasid or malat al-af‘al, more likely leads to bringing mudharat (negative) and, even, not given benefit for Muslim community as a whole. However, in practice, there are indications of deception that may not be aware of by the public. If this tendentious pattern accepts ideological pluralism would certainly not be problematic. But, in reality, they are seen as splitting-bamboo politics with a scenario according to their interests and status to promote their ideology. Also, it needs to highlight the comparison of fiqh and a mixture of ideologies or non-schools of thought. It is believed that this pattern has its benefits. On the other hand, people who are less well prepared on az-zari‘ah, will deal with their problems, which may lead to ideological chaos.